Adaptation of the Small Business Act for Europe: a comparison of four sectors of the Ukrainian economy - Lashin , Petro (Pressing Problems of Public Administration, 2025)
This article examines the asymmetric model of implementing Small Business Act for Europe principles in Ukraine through a comparative analysis of regulatory regimes and SME support outcomes across four key economic sectors. The research relevance stems from the need for scientific substantiation of optimal sectoral differentiation depth while simultaneously pursuing European integration objectives and ensuring economic resilience during wartime. The study aims to identify systemic consequences of parallel regulatory regimes formation across different economic sectors and their impact on state support resource utilization efficiency for SMEs. The research employs comprehensive analysis of empirical data from the OECD SME Policy Index 2024, official statistics on sectoral regime functioning (Diia.City, Brave1), and Ukraine Facility implementation indicators during 2021-2024. Three authorial principles of adaptive harmonization are applied: contextual equivalence, temporal synchronization, and proportionality of adaptation.The investigation reveals the emergence of four distinct patterns of European standards adaptation across sectors. The information technology sector demonstrates anticipatory digitalization through the Diia.City framework, establishing regulatory efficiency levels that surpass average European indicators while creating potential conflicts with emerging EU directives on platform employment. Defense technology experiences radical deregulation within the Brave1 cluster, prioritizing rapid innovation cycles over traditional quality control mechanisms. The industrial sector undergoes gradual harmonization preparing for ACAA implementation, though significant capacity gaps persist between large enterprises and SMEs regarding certification requirements. The agricultural sector faces adaptation pressure through sanitary and phytosanitary requirements while confronting paradoxical market access limitations.The theoretical framework of adaptive harmonization provides analytical tools for understanding how national institutional solutions achieve functional equivalence to traditional European support mechanisms without replicating their organizational forms. The principle of contextual equivalence explains the emergence of grant-based programs replacing European microcredit schemes, while temporal synchronization illuminates the parallel operation of crisis intervention instruments alongside structural reform mechanisms. The proportionality of adaptation principle reveals the rationality underlying resource concentration in sectors deemed critical for state survival and economic recovery.The findings demonstrate that sectoral differentiation enables concentration of limited administrative resources on critical priorities but generates risks of deepening structural disproportions and complicating intersectoral resource mobility. The effectiveness of Ukraine Facility financial resource absorption depends on alignment between sectoral adaptation depth and institutional capacity of SMEs to assimilate European support instruments. The study concludes that transition from situational experimentation with regulatory regimes toward strategic architecture design for SME support based on adaptive harmonization principles represents a necessary evolution for sustainable European integration while maintaining economic stability during ongoing military challenges.